NITRATE AND PHOSPHATE DISTRIBUTION RELATED TO FITOPLANKTON ABUNDANCE IN EAST YAPEN COASTAL WATER - Kalor, John Dominggus; Paiki, Kalvin (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2017)
The waters of Yapen Timur in Yapen Islands, Papua are semi-open waters with high potential natural resources. Recent research on chemical and biological parameters more specifically of nutrient concentration and phytoplankton abundance is still very limited. The study aimed to observe the concentration of nutrients (nitrates and phosphates), and their relation with the abundance of phytoplankton in Yapen Timur waters, was conducted on January 5Th to February 5th, 2016. Using explorative method and purposive sampling method, with 15 sampling points. Data analysis using Spectrophotometer at wavelength 545 nm for nitrate and 885 nm, whereas for phytoplankton abundance use APHA equation. Spatial distribution of nitrate, phosphate and phytoplankton abundance using kriging-method equation and Software Ermaper 7.0. Nitrate concentrations were found to be between 0.2 mg - 0.7 mg / l, phosphates ranging from 0.2 to 0.6 mg / l and the abundance of phytoplankton ranged from 49,682 to 139,490 ind / l. The correlation coefficient analysis indicates the relationship between nitrite and phytoplankton of 0.3947, phosphate and phytoplankton of. 0.0068. The concentration of nitrate and phosphate at the observation site indicated that the water quality belongs to the oligotrophic waters, the abundance of phytoplankton is high and there is no blooming in certain species, and the relationship between the nitrate and phosphate concentration is positively correlated with the abundance of phytoplankton at the observation site.